2000
DOI: 10.1046/j.1523-1755.2000.07704.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species as glucose signaling molecules in mesangial cells cultured under high glucose

Abstract: Reactive oxygen species as glucose signaling molecules in mes-stress is defined as a tissue injury induced by increase in angial cells cultured under high glucose.reactive oxygen species (ROS) such as hydrogen perox-Background. Oxidative stress is one of the important mediaide (H 2 O 2 ), superoxide anion (O 2 •Ϫ ), and hydroxyl radical tors of vascular complications in diabetes including nephrop-( • OH) and is one of the proposed mechanisms involved athy. High glucose (HG) generates reactive oxygen species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
208
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(218 citation statements)
references
References 61 publications
8
208
1
1
Order By: Relevance
“…Reactive oxygen species (ROS) and oxidative stress play a crucial role in diabetic pathophysiology [41] and play important role in high glucose-induced renal injury [42,43]. The present study demonstrated enhanced redox status within the kidney tissues of type 2 diabetic rats.…”
Section: Nc Group (N=10) Dm Group (N=4) Dm+afe Group (N=8) Dm+mfe Gromentioning
confidence: 58%
“…Reactive oxygen species (ROS) and oxidative stress play a crucial role in diabetic pathophysiology [41] and play important role in high glucose-induced renal injury [42,43]. The present study demonstrated enhanced redox status within the kidney tissues of type 2 diabetic rats.…”
Section: Nc Group (N=10) Dm Group (N=4) Dm+afe Group (N=8) Dm+mfe Gromentioning
confidence: 58%
“…Early activation of glomerular ERK1/2 in diabetes is suggested to play an important role in the progression of DN (33,35) and is consistent with a combined effect of high glucose and various growth factors, including IGF-1, PDGF-BB, and VEGF (23,54). Moreover, oxidative stress may play an important role in the progression of DN and emphasize the phosphorylation of ERK1/2 (27,28).…”
Section: Discussionmentioning
confidence: 75%
“…16 ROS have been shown to function as signaling molecules to activate several cellular stress-sensitive pathways that cause mesangial cell damage. 17 Besides, the oxidative stress resulting from increased ROS production can cause apoptosis in proximal tubular epithelial cells through pathways mediated by multiple caspases, such as caspase-3. 18 It has been shown that an increase in oxidative stress can induce apoptotic changes in HK2 cells, a novel human renal proximal tubular cell line, after being incubated in a high glucose concentration of 30 mmol/L for 18-48 h. 19 In contrast, decreased antioxidant activities are common events in diabetes.…”
Section: Discussionmentioning
confidence: 99%